Description of a new species of worm salamander (Caudata, Plethodontidae, Oedipina) in the subgenus Oedopinola from the central portion of the Cordillera Nombre de Dios, Honduras JAMES R. MCCRANIE & JOSIAH H. TOWNSEND (USA) - Mccranie, James R.; Townsend, Josiah H. (Zootaxa, 2011)
We describe a new species of Oedipina (subgenus Oedopinola) from Parque Nacional Pico Bonito in the central portion of the Cordillera Nombre de Dios in north-central Honduras. The new species was previously assigned to O. gephyra, but a combination of molecular analyses and its differences in foot morphology diagnose it from O. gephyra.